Exogenously applied 5-aminolevulinic acid mediated physiochemical regulations ameliorate weak light stress in tobacco seedlings - Li, Najia; Shahid, Muhammad; Zong, Xuefeng; Lv, Jun; Wang, Daibin; Saleem, Amna; Anjum, Shakeel Ahmad; Wang, Sangen (Bangladesh Journal of Botany, 2019)
Experiments were conducted to study the deleterious impacts of low intensity light on physiochemical and agronomic attributes of tobacco, to evaluate varying doses of foliar 5-aminolevulinic acid (5-ALA) for alleviation of adverse impacts of low light intensity and to observe either 5-ALA modulated physiochemical regulations impart stress tolerance at agronomic level. Significant decrease of biomass accumulation, synthesis of osmo-protectants, chlorophyll contents, and chlorophyll fluorescence and increase in malondialdehyde were recorded compared to control. Exogenous application of 5-ALA excellently alleviated adverse impacts of low light intensity stress on agronomic and physiochemical attributes of tobacco seedlings. Conclusively, Light stress had adverse implications on all studied attributes while 5-ALA at 10-20 mg/l had remarkable alleviated deleterious impacts of light stress on plant.